Constructing comprehensive venom proteome reference maps for integrative venomics. (3rd September 2015) - Eichberg, Susann; Sanz, Libia; Calvete, Juan J; Pla, Davinia
Abstract : Objective: Understanding the molecular basis of complex adaptive traits, such as snake venom, demands qualitative and quantitative comparisons of the temporal and spatial patterns of venom variation. Here, we assessed the proof–of-concept that locus-resolved reference venom proteome maps can be achieved through efficient pre-MS venom proteome decomplexation, peptide-centric MS/MS analysis and species-specific database searching. Methods: Venom proteome components were fractionated and quantified by RP-HPLC, SDS-PAGE and 2DE prior to LC-MS/MS matching against a species-specific transcriptomic dataset. Results: Combination of RP-HPLC/SDS-PAGE and 2DE followed by LC-MS/MS showed the existence of ∼178–180 venom protein species generated from ∼48 unique transcripts. Conclusions: Our results underscore that if sufficient pre-MS and MS efforts are applied, comprehensive venom maps can be achieved. And – equally important – dissociating the venom decomplexing steps from the protein identification process represents the key to achieving a quantitative and locus-resolved insight of the venom proteome.